2016
DOI: 10.5694/mja15.01336
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐hospital thrombolysis in ST‐segment elevation myocardial infarction: a regional Australian experience

Abstract: PHT can be delivered safely by paramedical staff in regional and rural Australia with good clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 17 publications
0
13
0
1
Order By: Relevance
“…Our experience is unique, as Australia has a different geography from the rest of the developed world, with the biggest challenge being the large transport distances in the rural and regional areas . We previously reported that PHT could be delivered successfully by paramedical staff in the regional settings with excellent clinical outcomes at 1 year . This sustained clinical benefit to over 6 years presented herein endorses the spread of the PHT approach to other healthcare networks where provision of timely primary PCI remains challenging.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Our experience is unique, as Australia has a different geography from the rest of the developed world, with the biggest challenge being the large transport distances in the rural and regional areas . We previously reported that PHT could be delivered successfully by paramedical staff in the regional settings with excellent clinical outcomes at 1 year . This sustained clinical benefit to over 6 years presented herein endorses the spread of the PHT approach to other healthcare networks where provision of timely primary PCI remains challenging.…”
Section: Discussionmentioning
confidence: 60%
“…In 2008, we introduced a system of care to provide early reperfusion to our STEMI patients; this involves pre‐hospital diagnosis and triage by paramedics using 12‐lead electrocardiogram (ECG) followed by either pre‐hospital thrombolysis (PHT) in the ambulance or primary PCI, according to their travel time to the CCL. We have already published 1‐year outcomes on our patients (PHT vs primary PCI) and the aim of the current analysis is to report our extended follow up.…”
Section: Introductionmentioning
confidence: 99%
“…Es extremadamente importante tener siempre in mente que el objetivo final es la reperfusión ya sea con fibrinólisis PH o ACP. En los pacientes en los cuales la ACP no es factible dentro de los intervalos de tiempo recomendados, como es al caso en muchos lugares de Chile, debe realizarse, de ser posible, fibrinolisis PH, como está bien descrito en las guías del MINSAL 11 y otras publicaciones que confirman la mayor efectividad de la fibrinolisis PH que en el hospital 4, [33][34][35][36][37][38][39] .…”
Section: Fibrinolisis Prehospitalariaunclassified
“…The Hunter New England health district covers an area of 130,000 square kilometres served by a single PPCI centre. The prehospital triage of patients in the Hunter region presenting with STEMI to the New South Wales Ambulance Service (NSWAS) has been described in detail previously [ 2 ]. Briefly, paramedics record a 12-lead electrocardiogram for all patients with symptoms suggestive of myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%